Association of OSMR Gene Polymorphisms with Rheumatoid Arthritis and Systemic Lupus Erythematosus Patients. (February 2014) - Lin, Yuan-Zhao; Li, Ruei-Nian; Lin, Chia-Hui; Ou, Tsan-Teng; Wu, Cheng-Chin; Tsai, Wen-Chan; Liu, Hong-Wen; Yen, Jeng-Hsien
Abstract Cytokines are involved in the pathogenesis of autoimmune diseases. Oncostatin M receptor (OSMR) activates JAK/STAT and MAPK pathways leading to the stimulation of a variety of cytokines and inflammatory substances. Many pro-inflammatory cytokines are involved in the inflammatory process of rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). In this study, we carried out experiments to examine the relationship of OSMR promoter polymorphisms with RA and SLE patients. 241 patients of RA, 143 patients of SLE and 203 healthy controls were enrolled in their recruitment from the Kaohsiung Medical University Hospital. Genomic DNA was extracted from peripheral blood mononuclear cells and gene polymorphism was genotyped by TaqMan real-time polymerase chain reaction. The OMSR promoter region −100 G/T (rs22922016) genotype was in no relation to the susceptibility of RA, but −100 T/T (rs22922016) genotype could prevent the patients with sicca syndrome and the existence of anti-Ro antibodies. In contrast, the −100 G/T+T/T (rs22922016) genotypes were significantly associated with an increased risk of SLE (odds ratio, OR=1.62, 95% confidence interval (CI), 1.01–2.62). 94.38% of SLE patients with arthritis were belonged to the −1687C/C (rs540558) genotype. The T allele of promoter region −100 T/T (rs22922016) has protective effect and could ameliorate the disease condition in RA patients, whereas the same T allele was a risk allele in the susceptibility of SLE. The disease severity of rheumatoid arthritis and systemic lupus erythematosus can be partially affected by the OSMR promoter polymorphisms.